2011
DOI: 10.1016/j.jmr.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin labels for in-cell EPR by analysis of nitroxide reduction in cell extract of Xenopus laevis oocytes

Abstract: Spin-label electron paramagnetic resonance (SL-EPR) spectroscopy has become a powerful and useful tool for studying structure and dynamics of biomacromolecules. However, utilizing these methods at physiological temperatures for in-cell studies is hampered by reduction of the nitroxide spin labels and thus short half-lives in the cellular environment. Consequently, reduction kinetics of two structurally different nitroxides was investigated in cell extracts of Xenopus laevis oocytes using rapid-scan cw-experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 32 publications
0
69
1
3
Order By: Relevance
“…Similarly, in cells expressing proteins with the unnatural amino acid SLK-1, reduction of the EPR probe in cells and in lysate was reported, and prevented successful measurements in vivo [104,105,139]. It has been shown that 5-membered piperidine rings have improved stability in biological systems in comparison with the six membered pyrollidines typically used in DNP applications [140,141]. Substitution of the positions flanking the nitroxides radical with bulky moieties has been shown to increase resistance to reduction [142,143], and nitroxide spin tags based on these bulky tags may be promising for in cell DNP.…”
Section: Dnp In Cell Applications: Challenges and Opportunitiesmentioning
confidence: 99%
“…Similarly, in cells expressing proteins with the unnatural amino acid SLK-1, reduction of the EPR probe in cells and in lysate was reported, and prevented successful measurements in vivo [104,105,139]. It has been shown that 5-membered piperidine rings have improved stability in biological systems in comparison with the six membered pyrollidines typically used in DNP applications [140,141]. Substitution of the positions flanking the nitroxides radical with bulky moieties has been shown to increase resistance to reduction [142,143], and nitroxide spin tags based on these bulky tags may be promising for in cell DNP.…”
Section: Dnp In Cell Applications: Challenges and Opportunitiesmentioning
confidence: 99%
“…However, compared with in-cell PELDOR, the in-cell spFRET setup offers one particularly important advantage, namely extended measurement time. Whereas the in-cell spFRET measurement time is primarily limited by the life span of the cell (typically several hours for the ATTO680/ATTO740 donor–acceptor system used in this study), the in-cell PELDOR measurement time is typically limited to ∌70 min due to the rapid reduction of the spin labels by the cellular environment (3,4,42). …”
Section: Discussionmentioning
confidence: 99%
“…7,8) Eine der grĂ¶ĂŸten Schwierigkeiten bei intrazellulĂ€ren DEER-Experimenten in Kombination mit Nitroxid-Markierung liegt in der Reduktion des Nitroxids in der zellulĂ€ren Umgebung und der daraus resultierenden kurzen Lebensdauer der Spinmarkierung. Da dieser Reduktionsprozess enzymatisch ist, 9) fĂŒhren geringe Änderungen an der Struktur des Spinmarkers zu deutlichen Unterschieden in der Halbwertszeit in der Zelle. So weist der in Abbildung 1 gezeigte Spinmarker eine Halbwertszeit von etwa 30 Minuten auf, wĂ€hrend es das Ana-logon mit einem Sechsring auf eine Halbwertszeit von lediglich einer Minute bringt.…”
Section: Gepulste Experimenteunclassified